2010
DOI: 10.1901/jeab.2010.93-329
|View full text |Cite
|
Sign up to set email alerts
|

Semantic False Memories in the Form of Derived Relational Intrusions Following Training

Abstract: Contemporary behavior analytic research is making headway in characterizing memory phenomena that typically have been characterized by cognitive models, and the current study extends this development by producing "false memories" in the form of functional equivalence responding. A match-to-sample training procedure was administered in order to encourage participants to treat groups of unrelated English words as being interchangeable. Following training, participants were presented with a list of words from wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
34
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 64 publications
4
34
0
1
Order By: Relevance
“…This novel finding suggests that partial equivalence tests played a significant role in the production of false memories in the present procedure. As a whole, these data add further support to previous findings (Guinther & Dougher, , ) on derived relational responding as a behavioral model of false memories in the DRM paradigm (Roediger & McDermott, ). First, we discuss the remembering of study‐list words and nonstudy words across the three achievement groups.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This novel finding suggests that partial equivalence tests played a significant role in the production of false memories in the present procedure. As a whole, these data add further support to previous findings (Guinther & Dougher, , ) on derived relational responding as a behavioral model of false memories in the DRM paradigm (Roediger & McDermott, ). First, we discuss the remembering of study‐list words and nonstudy words across the three achievement groups.…”
Section: Discussionsupporting
confidence: 88%
“…Using the framework of derived relational responding, Guinther and Dougher (, ) developed the Derived Relational Intrusions Following Training (DRIFT) procedure as a behavior analytic account of semantic effects in false remembering. The DRIFT procedure posits that semantic false memory effects can occur when studied stimuli (e.g., words) acquire a discriminative function for remembering, and this function then transfers to stimuli that are members of the same equivalence class as the studied stimuli.…”
mentioning
confidence: 99%
“…Similarities regarding stimulus equivalence and cognitive network theories of memory have occasionally been noted in the literature on stimulus equivalence (Critchfield and Fienup 2008;Sidman 1994). With a few notable exceptions (Challies et al 2011;Guinther and Dougher 2010), few empirical studies approaching this link, however, have been published to date. Investigations of similarities and differences in the long-term stimulus control of behavior exerted by stimuli involved in stimulus equivalence classes and stimuli not known to enter into such classes may be a useful addition to the literature on memory phenomena and stimulus equivalence.…”
Section: Discussionmentioning
confidence: 99%
“…After an equivalence class has been established, a function given to one member of a class may transfer to other members of that class, including emotional responses (e.g., Amd, BarnesHolmes, & Ivanoff, 2013;Bortoloti & de Rose, 2009, 2012de Almeida & de Rose, 2015;de Rose et al, 1988;Dougher et al, 1994;Wulfert & Hayes, 1988). Research on fear and anxiety has indicated that fear evoked by a member of a class of equivalent stimuli transfer to the other members (e.g., Bennett, Meulders, Baeyens, & Vlaeyen, 2015;Dymond, Dunsmoor, Vervliet, Roche, & Hermans, 2015;Guinther & Dougher, 2010), an effect some of these authors called symbolic, or category-based generalization (see Dymond et al, 2015). The studies of BarnesHolmes et al (2000) and Smeets and BarnesHolmes (2003) as well as the present study indicate that the same effect can account for the acquisition of positive emotional functions by brands related to attractive characters.…”
Section: Discussionmentioning
confidence: 99%